Promotion and development strategy for 5 prioritized tourist attraction in Kotabaru Regent - Andini Risfandini (Jurnal Pariwisata Pesona, 2022)
The decrease number of tourists’ visit in Kotabaru district, in the year of 2020 due to COVID-19 pandemic serves as the background of this research.The aim of this research is to compose a marketing and development strategy of 5 priority tourist destinations in Kotabaru district South Borneo province namely: Siring Laut Saijaan beach, Gedambaan beach, Samber Gelap beach, Tamiang bay, and Tanjung Kunyit bay. This research is using a quantitative approach with a survey questionnaire as a tool for data collection using a Likert scale to measure tourists’ perception of 5 aspects namely: attraction, amenities, accessibility, image, price, tourist satisfaction on the 5 priority tourist destinations in Kotabaru district. This research combine marketing and development strategy investigation by using demography and tourists’ perception analysis of those 5 aspects. The result of this research concludes that an effective promotion strategy using market segmentation, the development of four aspects such as attraction, amenities, accessibility, image with reasonable price will improve the quality of tourist destination which subsequently will increase the number of tourists visiting.